Sterol and Triterpene Profiles of the Callus Culture of Solanum mammosum - Juliana, Silvy; Suciati,; Indrayanto, Gunawan (Makara Journal of Science, 2019)
This study aimed to compare the sterol and triterpene profiles of two types of Solanum mammosum callus cultures , i.e., compact globular structure (CGS) and normal fine (F) calluses. The CGS callus resulted from the differentiation of the F calus culture after many years of subculturing. The growth rate, microscopic characteristics, and morphologies of the two callus types were determined and compared. Sterols and triterpenes were identified through thin-layer chromatog-raphy, gas chromatography-flame ionization detection, and gas chromatography–mass spectrometry analyses. The growth rate of the CGS callus was lower than that of the F callus. Microscopic identification revealed that thick, lignincontaining cell walls formed in the CGS callus but not in the F callus. The chromatographic analysis suggested that the CGS and F callus cultures had different sterol and triterpenoid profiles. The sterols and triterpenes produced by the CGC culture were more diverse than those produced by the F callus culture